2019
DOI: 10.1016/j.molp.2018.12.024
|View full text |Cite
|
Sign up to set email alerts
|

The barren stalk2 Gene Is Required for Axillary Meristem Development in Maize

Abstract: The diversity of plant architecture is determined by axillary meristems (AMs). AMs are produced from small groups of stem cells in the axils of leaf primordia and generate vegetative branches and reproductive inflorescences. Previous studies identified genes critical for AM development that function in auxin biosynthesis, transport, and signaling. barren stalk1 (ba1), a basic helix-loop-helix transcription factor, acts downstream of auxin to control AM formation. Here, we report the cloning and characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 94 publications
(208 reference statements)
0
28
0
Order By: Relevance
“…The different severity of FM defects in mutants of Arabidopsis , maize or sunflower could be related to the distinctive inflorescence architecture of these three species (Hernández & Green, 1993;McSteen & Hake, 2001; Wang et al, . ; Yang et al, 2012; Yao et al, ). The raceme of Arabidopsis is an indeterminate inflorescence, where apical meristem grows indefinitely, generating a continuous main axis that laterally produces FMs after a single branching step (Long & Barton, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The different severity of FM defects in mutants of Arabidopsis , maize or sunflower could be related to the distinctive inflorescence architecture of these three species (Hernández & Green, 1993;McSteen & Hake, 2001; Wang et al, . ; Yang et al, 2012; Yao et al, ). The raceme of Arabidopsis is an indeterminate inflorescence, where apical meristem grows indefinitely, generating a continuous main axis that laterally produces FMs after a single branching step (Long & Barton, ).…”
Section: Discussionmentioning
confidence: 99%
“…In rice, LAX1 physically interacts with LAX2 a plant‐specific nuclear factor (Tabuchi et al, ). Different genes regulate ZmBA1 that is also transcriptionally regulated by auxin (reviewed by McSteen, 2010); recently, Yao et al () demonstrated that the BA2 contains a protein–protein interaction domain and physically interacts with BA1. The maize gene BA2 is the ortholog of the rice LAX2 gene but notably, the closest orthologs of BA2 / LAX2 in the dicot Arabidopsis have not yet been functionally characterized (Yao et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The BA1 homolog in rice, LAX PANICLE 1 (LAX1) also promotes initiation of lateral organs (Komatsu et al 2003). In maize and rice, similar BA1/LAX1 interacting nuclear proteins with putative RAWUL/PDZ/ SH3 domains called BA2 (Yao et al 2019) or LAX2 (Tabuchi et al 2011) were identified. LAX2 links to auxin response in other processes by blocking the interaction between Aux/IAA proteins and ARFs (Li et al 2018).…”
Section: Lateral Organ Initiationmentioning
confidence: 99%